Overview of the Application Student Fatigue Surveillance at High School - Ayik Mirayanti Mandagi; Lucia Yovita Hendrati; Jayanti Dian Eka Sari; Nurul Fitriyah; Sarda Ika Devi; Syahrul Ramadhan (Universitas Ahmad Dahlan, 2023)
The World Health Organization (WHO) declared that this epidemic is a public health emergency of international concern on January 31, 2020 (Bulut & Kato, 2020). As of July 15, 2022, a new coronavirus infection, COVID-19, has spread worldwide, causing more than 500 million cases and over 6.3 million deaths. The COVID-19 pandemic situation presents many challenges and unprecedented social distancing problems that have changed habits, one of which is in the field of education. During the COVID-19 pandemic, learning was carried out online according to the direction of the Ministry of Education and Culture. All educational activities began to use video conferencing, mobile based, and computers/smartphones. The transition of the original learning system offline to online requires students to adapt to these conditions. This has a negative impact, one of which is fatigue in students. The impact of student fatigue causes a sense of loss of spirit, laziness, stress, insomnia. This research was carried out in 2020 with a data collection technique, namely using a Focus Discussion Group (FGD) on the head/leader of a senior high school (SMA) in the East Java area with a total of 8 informants. The results of the FGD found that Some of the schools do not yet have a student fatigue monitoring program. Some schools are not yet aware of the importance of student resilience surveillance. Therefore, it is necessary to have a policy of requiring each school to carry out health surveillance, especially related to student conditions so that bias is well monitored the condition of students, both physical and mental, in order to follow optimal learning.